1997
DOI: 10.1074/jbc.272.48.30283
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Structure of HIV-1 Tat Is Required for Suppression of CD26-dependent T Cell Growth

Abstract: Evidence exists that the human immunodeficiency virus-1 (HIV-1) transactivator Tat occurs extracellularly and is involved in the immunosuppression of non-HIV-1-infected T cells of acquired immunodeficiency syndrome (AIDS) patients. The mechanism of this immunosuppressive activity of Tat has been controversially discussed. Interestingly, Tat binds to the T cell activation marker CD26, which has been shown to play a key role in the regulation of growth of lymphocytes and to inhibit its dipeptidyl peptidase IV (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…In spite of this, the overall effect of Tat in patients infected by HIV-1 appears rather suppressive. This can be explained by the inhibition of the proliferative T response (52,56), the induction of T-lymphocyte apoptosis (26), the inhibition of phagocytosis of apoptotic bodies by dendritic cells (58), the cytotoxic activity of NK cells (59), and finally the suppression of IL-12 production by dendritic cells (45) and monocytes (31). The effect of Tat on IL-10 production reported here agrees with all of these reports concerning the potential immunosuppressive role of Tat during infection by HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, the overall effect of Tat in patients infected by HIV-1 appears rather suppressive. This can be explained by the inhibition of the proliferative T response (52,56), the induction of T-lymphocyte apoptosis (26), the inhibition of phagocytosis of apoptotic bodies by dendritic cells (58), the cytotoxic activity of NK cells (59), and finally the suppression of IL-12 production by dendritic cells (45) and monocytes (31). The effect of Tat on IL-10 production reported here agrees with all of these reports concerning the potential immunosuppressive role of Tat during infection by HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The amino terminus (aa 1 to 20), cysteine-rich domain (aa 21 to 40), and core region (aa 1 to 48) together constitute the minimal activation domain for transcription in vitro (30). The N-terminal portion of Tat binds cell surface CD26 with high affinity and is believed to be responsible for CD26-mediated immunosuppressive activity (26,49,57). The cysteine-rich domain has homology to chemokines and mediates binding to chemokine receptors (1,2,16).…”
mentioning
confidence: 99%
“…By the use of peptides spanning specific domain of the Tat structure or of functional blocking antibodies, some investigators demonstrated that Tat binding to integrin through the RGD sequence near the C terminus (7,62) is relevant for the activation of lymphocytes (70), EC (5, 13), monocytes (6,35), and neuronal cells (48). Through its N-terminal structure, Tat interacts with dipeptidyl peptidase IV, located on the T cell surface, and suppresses antigen-induced cell activation (26,68). Additionally, Tat binds to and activates the tyrosine kinase receptors encoded by the KDR and Flt-1 genes in EC and Kaposi's sarcoma cells (4,21) and monocytes (43), respectively.…”
mentioning
confidence: 99%